Evaluation of cost effectiveness and efficacy of commonly used different antacid gel preparations - H, Vedavathi; S, Tejasvi T; Revankar, Shreenivas P. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Gastroesophageal reflux disease (GERD) is a common clinical condition in Indian population. Antacids, which are available as over the counter (OTC) are the commonly prescribed drugs for treatment of GERD. Antacids manufactured and marketed by various multinational and local companies are available in the market. There is need for evaluating the cost effectiveness and efficacy of these antacids as a matter of public concern. Hence the present study was conducted to evaluate the cost effectiveness and efficacy of the commonly prescribed antacid gel preparations. Methods: Seven different gel formulations of antacids manufactured by different companies were evaluated. Cost effectiveness was done by calculating the cost per ml of antacid and also by palatability test. Efficacy was evaluated based on acid neutralizing capacity (ANC) of antacid preparations. Results: The highest cost was 0.305 Rs. per ml and lowest was 0.135 Rs per ml. Palatability score was high at 26.80 and low at 23.85. The antacid with lowest ANC was 20.5 mEq and the highest was 26.5 mEq. Conclusion: Cost effectiveness studies are beneficial in improving the prescribing pattern. It will be a benefit for both doctor as well as patient.